1986
DOI: 10.1016/0035-9203(86)90266-x
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and kwashiorkor: clinical studies in Sudanese children

Abstract: Aflatoxin analysis of blood and urine by high performance liquid chromatography in 584 Sudanese children is reported. The results in 404 malnourished children comprising 141 kwashiorkor, 111 marasmic kwashiorkor and 152 with marasmus are compared with 180 age-matched controls and correlated with clinical findings. The aflatoxin detection rate and mean concentration were higher in serum of children with kwashiorkor than the other groups. The difference between the detection rate in kwashiorkor and controls was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Because of the liver's involvement, it was suggested that AFB 1 may be involved (Hendrickse et al, 1983). This appeared to be supported by other observation, e.g., relating peak prevalence for kwashiorkor with climatic conditions such as high humidity (de Vries and Hendrickse, 1988); general occurrence of AFB 1 in children's excreta (de Vries et al 1987(de Vries et al , 1990; liver (Lamplugh and Hendrickes, 1982); serum (Coulter et al, 1986;Hatem et al, 2005); and its reduced product, aflatoxicol, in livers of Ghanaian children (Apeagyei et al, 1986).…”
Section: Kwashiorkorsupporting
confidence: 57%
“…Because of the liver's involvement, it was suggested that AFB 1 may be involved (Hendrickse et al, 1983). This appeared to be supported by other observation, e.g., relating peak prevalence for kwashiorkor with climatic conditions such as high humidity (de Vries and Hendrickse, 1988); general occurrence of AFB 1 in children's excreta (de Vries et al 1987(de Vries et al , 1990; liver (Lamplugh and Hendrickes, 1982); serum (Coulter et al, 1986;Hatem et al, 2005); and its reduced product, aflatoxicol, in livers of Ghanaian children (Apeagyei et al, 1986).…”
Section: Kwashiorkorsupporting
confidence: 57%
“…Also rejecting protein deficiency, Hendrikse 38 proposed that kwashiorkor was due to aflatoxin poisoning because he found higher circulating levels of aflatoxin in kwashiorkor than marasmus. However, these results are more likely to be explained by the liver dysfunction and failure to metabolise aflatoxin in kwashiorkor, because the excretion of aflatoxicol in the urine is the same in the two conditions 39 . Liver samples sent to Hendrikse from Jamaica for blind analysis did not support this aetiology (Table 1).…”
Section: Protein Deficiencymentioning
confidence: 87%
“…There are several other studies of some note with respect to aflatoxin and birth outcomes with several showing significant negative correlations between birth anthropometry or child undernutrition and aflatoxin measures in biofluids [32–34, 38, 41, 42, 62, 133, 134], whilst one reported study found no statistically significant associations [135]. Importantly, this current set of studies used only “aflatoxin biomeasures” and none of these studies used validated exposure biomarker (AF-albumin in sera, AF-N7-Guanine in urine, nor AFM1 in urine) to assess the level of aflatoxin exposure; thus, quantitative relationships between the biomeasure and exposure outcome are not straightforward to interpret.…”
Section: Epidemiology Of Aflatoxin Driven Growth Falteringmentioning
confidence: 99%